Case report: Corpectomy and iliac crest bone autograft as treatment for a vertebral plasma cell tumor in a dachshund dog - Yoder, Hannah R.; MacRae, Megan R.; Snead, Olivia M.; Kraus, Karl H. (Frontiers in Veterinary Science, 2023)
A seven-year-old, 7.5kg, female spayed dachshund dog presented to a veterinary teaching hospital after being referred for lameness and the inability to urinate. The dog presented as weakly ambulatory paraparetic with intact pain perception. Computed tomographic (CT) imaging showed ventral bony lysis and periosteal proliferation of the L3 vertebra consistent with a plasma cell tumor. A corpectomy of the L3 vertebra was performed and subsequently stabilized with autogenous cortico-cancellous iliac crest bone staves, autogenous cancellous bone, and bilaterally placed locking plates (String-of-Pearls (SOP), Orthomed). The dog recovered well with a no decrease in neurologic status overnight and continued to improve until discharge. Upon recheck exam at four weeks postoperatively, the dog appeared neurologically improved with only mild ambulatory proprioceptive ataxia of the hind limbs. This case demonstrates that transposition of a non-vascularized iliac crest autogenous bone graft with stabilization via SOP plates and screws can be used in the management of dogs with vertebral plasma cell tumors and should be considered as a surgical option in similarly affected cases.Corpectomy and iliac crest bone autograft as treatment for a vertebral plasma cell tumor